Synthesis of Ziziphus spina-christi (Jujube) Root Methanol Extract Loaded Functionalized Silver Nanoparticle (ZS-Ag-NPs); Physiochemical Characterization and Effect of ZS-Ag-NPs on Adipocyte Maturation, Adipokine and Vascular Smooth Muscle Cell Interaction - Abu ElGasim Ahmed Yagoub; Ghedeir Muslem Alshammari; Pandurangan Subash-Babu; Mohammed Awad alkareem Mohammed; Mohammed Abdo Yahya; Aesha Ibrahim Alhosain (Nanomaterials, 2021)
In this research, a simple, green approach was employed to synthesize silver nanoparticles with the aid of Ziziphus spina-christi (L.) methanol root extract, which can act as a reducing, capping agent to treat obesity and inflammation. Globally, Ziziphus spina-christi (Jujube) root is used in traditional therapy as a lipolysis promoter. GC-MS results confirmed the availability of kaempferol (flavonol), cannabinol and indole-3-carboxylic acid in Ziziphus spina-christi root methanol extract (ZSE). ZSE silver nanoparticles (ZS-Ag-NPs) were synthesized and their effect on mitochondrial fatty acid oxidation capacity and adipokine levels in maturing adipocytes were analyzed. Maturing adipocytes treated with 0.4 µg/dL of ZSE and ZS-Ag-NPs significantly reduced the lipid content in adipocytes by 64% and 82%, respectively. In addition, lipolysis-related genes such as LPL (1.9 fold), HSL (2.3 fold), PGC-1α (3 fold), UCP-1 (4.1 fold), PRDM16 (2 fold) and PPARα (2.7 fold) increased significantly in ZS-Ag-NPs treated maturing adipocytes. The ZS-Ag-NPs treatment significantly decreased insulin resistance and metabolic inflammation-related LTB4-R, TNF-α, IL-4 and STAT-6 mRNA levels. Mitochondrial thermogenesis stimulating capacity of ZS-Ag-NPs was further confirmed by the significantly enhanced CREB-1 and AMPK protein levels in adipocytes. Furthermore, ZS-Ag-NPs treated adipokines (condition media, CM) were treated with human umbilical vein endothelial cells (HUVECs) to determine cytotoxicity and pro-inflammatory stimulus capacity. We found that ZS-Ag-NPs treated adipocyte CM effectively increased mRNA expression levels of the vascular endothelial cell growth factor (VEGF), and down-regulated oxidative stress (LPO, eNOS, and HO) and vascular cell inflammation (ICAM, VCAM, TNF-α, IL-1β, and NF-κB). In conclusion, ZS-Ag-NPs displayed an action at the molecular level in mitochondrial fatty acid oxidation, decreased adipokine secretion in adipocytes, and enhanced vascular endothelial cell growth. This molecular mechanical action of ZS-Ag-NPs reduced effectively obesity progressions and metabolic inflammatory pathogenesis associated with aging.